2010
DOI: 10.1017/s1368980010002569
|View full text |Cite
|
Sign up to set email alerts
|

A workplace feasibility study of the effect of a minimal fruit intervention on fruit intake

Abstract: Objective: The main purpose of the study was to investigate the feasibility of using workplaces to increase the fruit consumption of participants by increasing fruit availability and accessibility by a minimal fruit programme. Furthermore, it was investigated whether a potential increase in fruit intake would affect vegetable, total energy and nutrient intake. Design: A 5-month, controlled, workplace study where workplaces were divided into an intervention group (IG) and a control group (CG). At least one piec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 17 publications
5
51
0
Order By: Relevance
“…The positive finding regarding fruit intake were supported by two other studies 60 61. Both offered free fruit at the workplace aimed to promote fruit intake by increasing availability and accessibility.…”
Section: Discussionmentioning
confidence: 67%
“…The positive finding regarding fruit intake were supported by two other studies 60 61. Both offered free fruit at the workplace aimed to promote fruit intake by increasing availability and accessibility.…”
Section: Discussionmentioning
confidence: 67%
“…In the present workplace intervention the overall aim was to increase fruit intake by making it freely available and accessible to intervention participants, no other information was made available [24]. The focus on increasing fruit intake in this dietary intervention was because of the known health benefits of fruit consumption, particularly in terms of the inverse association between fruit intake and body weight [25].…”
Section: Introductionmentioning
confidence: 99%
“…This change is relevant according to the WHO, who states that there is convincing evidence that a diet high in fruit and vegetables reduces the risk of obesity, diabetes and cardiovascular disease 4. More recently, others have shown that a minimal intervention, such as providing free fruit at the workplace, increases average fruit intake44 and may decrease body weight 45. As fruit consumption has declined in the Netherlands,18 we recommend increasing workplace fruit availability and accessibility as an effective low-cost alternative in the guideline besides education and counselling.…”
Section: Discussionmentioning
confidence: 97%